1997
DOI: 10.4049/jimmunol.159.12.6112
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses induced by intramuscular or gene gun injection of protective deoxyribonucleic acid vaccines that express the circumsporozoite protein from Plasmodium berghei malaria parasites.

Abstract: The circumsporozoite protein (CSP) is a target for effector Ab and cell mediated immunity against malaria parasites; DNA vaccination can induce both types of effector response. The immunogenicity and efficacy of two DNA plasmids expressing different amounts of Plasmodium berghei CSP were evaluated by immunizing BALB/c mice i.m. or epidermally and by varying the number of immunizations (one to three doses) and the interval between immunizations. Expanding the interval gave the strongest effect, increasing effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Injection with DNA vaccines leads to lower but longer in vivo expression of the encoded Ags, and, since DNA vaccination takes longer to induce Ab immune responses, it may take longer for avidity increases to become apparent. In support of this possibility, Lyon and his colleague recently reported that increasing the interval between DNA immunization of mice increased the levels of Abs produced (57). To address the issue of longer intervals between DNA injections, we have done an experiment with the V3 DNA vaccine, immunizing three times at weeks 0, 12, and 32.…”
Section: Discussionmentioning
confidence: 99%
“…Injection with DNA vaccines leads to lower but longer in vivo expression of the encoded Ags, and, since DNA vaccination takes longer to induce Ab immune responses, it may take longer for avidity increases to become apparent. In support of this possibility, Lyon and his colleague recently reported that increasing the interval between DNA immunization of mice increased the levels of Abs produced (57). To address the issue of longer intervals between DNA injections, we have done an experiment with the V3 DNA vaccine, immunizing three times at weeks 0, 12, and 32.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancement of CD4 (helper) T cell response may in turn enhance B and CD8 T cell responses as CD4 T (T helper) cells are involved in the stimulation of both B and CD8 T cells [ 25 ]. Previous studies showed that the inclusion of a secretory signal sequence in the immunogen enhanced the induction of immune responses when compared to the non-secretory forms [ 26 , 27 ]. Thus, it is useful to address whether a PCV2 capsid-based immunogen would be more immunogenic in a secreted form.…”
Section: Introductionmentioning
confidence: 99%